Rose with Thorns: Phenomenological Study Regarding Being a Preschool Teacher in Rural Areas in Turkey - Sevcan Yağan Güder (Anı Publishing, 2019)
The main purpose of this study is to reveal the experiences of pre-school teachers who teach in rural areas. Phenomenology design, which is one of the qualitative research designs, was used in this study. This study included 9 pre-school teachers who performed teaching profession in Diyarbakır, Ordu, Van, Bursa, Şanlıurfa and Ağrı provinces between 2016-2017 educational year. The data of the study were collected via semi-structured interviews which were conducted through the Skype program. The results of this study indicate that teaching in the rural areas gives high level of spiritual satisfaction; on the other hand, it is a difficult process that contributes to professional development of the teachers. Teachers also expressed that they experienced language and communication problems with both parents and children and that they had problems with regard to heating, water, electricity, unsuitable class environments and teaching material deficiencies.